Der Zeitraum der Nichtleistung Pflichtverletzung wegen Nichtleistung im allgemeinen Leistungsstörungs- und Insolvenzrecht - Felsch, Johannes Claudio (Mohr Siebeck, 2024)
The breach of duty due to non-performance is of a permanent nature, lasting until its termination ex nunc or ex tunc. Johannes Claudio Felsch develops a fresh (time-related) systemisation of the rights arising from irregularity of performance and the legal objections against it, finishing off by transferring this system to insolvency law.
PublicationDate: 20240531
Keywords: Leistungsstörungsrecht -- Warenverkehrsfreiheit -- Höchstrichterliche Leitsätze -- Einwendungen -- Sonderprozessrecht -- Insolvenzvertragsrecht -- Insolvenzverwalterwahlrecht -- Leistungspflichtverletzung -- Mittelalterliche Religion -- Bürgerliches Recht -- Zivilverfahrensrecht, Insolvenzrecht